2017
DOI: 10.1038/s41598-017-02268-0
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of diets with low advanced glycation end products improves cardiometabolic parameters: meta-analysis of randomised controlled trials

Abstract: Studies examining the effects of consumption of diets low in advanced glycation end products (AGEs) on cardiometabolic parameters are conflicting. Hence, we performed a meta-analysis to determine the effect of low AGE diets in reducing cardiometabolic risk factors. Seventeen randomised controlled trials comprising 560 participants were included. Meta-analyses using random effects models were used to analyse the data. Low AGE diets decreased insulin resistance (mean difference [MD] −1.3, 95% CI −2.3, −0.2), tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 41 publications
(230 reference statements)
2
52
0
2
Order By: Relevance
“…97 A recent meta-analysis of randomized controlled trials revealed that consumption of a low-AGE diet decreased the levels of total cholesterol, circulating AGEs, and inflammatory and oxidative stress biomarkers, such as tumor necrosis factor-α, soluble vascular cell adhesion molecule-1, and 8-isoprostanetotal, in patients with and without type 2 diabetes. 98 Aptamers are short, single-stranded RNA or DNA oligonucleotides that can bind to various proteins, peptides, and viruses with high specificity and affinity. 99-101 DNAaptamers directed against AGEs and RAGE (AGE-aptamers and RAGE-aptamers) that attenuate the interaction of AGEs with RAGE in vitro have been recently developed (Figure 3).…”
Section: Disclosuresmentioning
confidence: 99%
“…97 A recent meta-analysis of randomized controlled trials revealed that consumption of a low-AGE diet decreased the levels of total cholesterol, circulating AGEs, and inflammatory and oxidative stress biomarkers, such as tumor necrosis factor-α, soluble vascular cell adhesion molecule-1, and 8-isoprostanetotal, in patients with and without type 2 diabetes. 98 Aptamers are short, single-stranded RNA or DNA oligonucleotides that can bind to various proteins, peptides, and viruses with high specificity and affinity. 99-101 DNAaptamers directed against AGEs and RAGE (AGE-aptamers and RAGE-aptamers) that attenuate the interaction of AGEs with RAGE in vitro have been recently developed (Figure 3).…”
Section: Disclosuresmentioning
confidence: 99%
“…As of now, several clinical trials testing the effects of a low AGE diet have been published in the literature and demonstrate that consumers can be educated as to how to use low-AGE-generating cooking methods such as poaching, steaming, stewing, and boiling without many problems. 43,49 Moreover, taste can be markedly improved by the sparing use of herbs, condiments and spices, some of which may have intrinsic antiglycation activity. 50 Of interest, pretreatment of food with acidic marinades such as lemon, vinegar or tomato juice prior to cooking significantly limits the increase in AGE content when baking meat, for example.…”
Section: Dietary Agesmentioning
confidence: 99%
“…A common critique to a dietary intervention that relies on changing culinary technique is that patients will not follow it, because cooking is a cultural behavior too difficult to change. As of now, several clinical trials testing the effects of a low AGE diet have been published in the literature and demonstrate that consumers can be educated as to how to use low‐AGE‐generating cooking methods such as poaching, steaming, stewing, and boiling without many problems . Moreover, taste can be markedly improved by the sparing use of herbs, condiments and spices, some of which may have intrinsic antiglycation activity .…”
Section: Introduction To the Concept Of An Aspirational Diet For Dialmentioning
confidence: 99%
“…Important producers of inflammatory adipokines are ATMs, which are strongly increased in the vAT of obese mice and humans 3,76 . Local proliferation of ATMs and infiltration followed by differentiation of bone marrow-derived monocytes both contribute to these elevated levels of ATMs 77,78 . Although it is not yet fully understood what triggers the increased infiltration and proliferation of ATMs during obesity, AT hypertrophy during AT expansion causes hypoxia and adipocyte cell death, both capable of triggering AT inflammation 7,79 .…”
Section: Adipose Tissue Inflammationmentioning
confidence: 99%
“…Many parameters including circulating AGEs and immune cells, liver enzymes and LGI markers will be measured. A recent meta-analysis focused on cardiometabolic parameters already reported beneficial effects of low AGE consumption on LGI markers, but liver function or damage was not studied 77 . The aforementioned clinical studies will provide crucial information about favorable effects of AGE reduction on liver disease.…”
Section: Future Directionsmentioning
confidence: 99%